Information technology. International standardized profiles FVT2nn. Virtual terminal basic class. Register of control object type definitions. FVT2116. Generalized Telnet Synch Control Object; FVT2117. Generalized Telnet Signal Control Object; FVT2118. Generalized Telnet Negotiation Control Object; FVT2119. Generalized Telnet Subnegotiation Control Object Part 12, (15th November 1995) - British Standards Institution,
No abstract available